Analysis of Fatigue Damage on Test Sections Submitted to HVS Loading - Wojciech Bańkowski; Marcin Gajewski; Dariusz Sybilski (The Baltic Journal of Road and Bridge Engineering)
This paper presents results of field tests performed in Poland within SPENS project. The test sections were built in Poland (October 2007). All of construction works as well as research tests were conducted in cooperation with the Swedish National Road and Transport Research Institute (VTI), STRABAG, TPA, Lafarge and ORLEN. The test section was divided into four parts of the same layer thickness, but with two different mixes in the base course: asphalt concrete and high modulus asphalt concrete. This allowed direct evaluation of the influence of high modulus asphalt concrete on pavement durability. Tests sections were subjected to accelerated loading test with use of the Heavy Vehicle Simulator. These tests were accompanied by field tests (Falling Weight Deflectometer and Ground-Penetrating Radar) and numerous of laboratory tests (binder content, grading, air voids, resistance to rutting, stiffness and fatigue). Investigation of fatigue damage development of asphalt layers is also presented. Four pavement structures with different binder courses made of: high modulus asphalt concrete with grains up to16mm and 20/30 binder, asphalt concrete with grains up to16 mm and binder 35/50 and fine graded anti-fatigue layer were compared using accelerated tests and also verification of applied design methods was made.